Yellow chili bell pepper (Capsicum baccatum) on productive and pigment parameters in broiler chickens in the Peruvian highlands - Moisés Mendoza Alvarez; Jordan Ninahuanca Carhuas; Armando Aquino Tacza (Veterinary Integrative Sciences)
The present study aimed to determine the effect of yellow chili pepper (Capsicum baccatum) as a natural pigment in the diet of broiler chickens. The study was conducted at the Yauris Experimental Station of the Universidad Nacional del Centro del Perú. A total of 120 animals were used, distributed across four treatments with the inclusion of yellow chili pepper flour (T0 = 0%, T1 = 10%, T2 = 15%, and T3 = 20%). The initial weights of the chickens were homogeneous across all groups. However, significant statistical differences were observed in weight gain (P<0.05), with the T3 group achieving the highest weight gain of 2,493.3 g. Similarly, for final weight, the T3 group showed superior results with 2,604.1 g, and for carcass weight, T3 was outstanding with 2,484.2 g. The amount of β-carotene in the leg region was highest in the T3 group at 0.0716 mg/100g, and in the breast region, T3 also showed the highest amount with 0.046 mg/100g. In conclusion, the inclusion of yellow chili pepper flour in the diet of broiler chickens not only increases weight gain and carcass yield but also enhances the β-carotene content in the meat, serving as an effective natural pigment.